Baseline investigation on soil solidification through biocementation using airborne bacteria - Chen, Meiqi; Gowthaman, Sivakumar; Nakashima, Kazunori; Takano, Chikara; Kawasaki, Satoru (Frontiers in Bioengineering and Biotechnology, 2023)
Microbial induced carbonate precipitation (MICP) through the ureolysis metabolic pathway is one of the most studied topics in biocementation due to its high efficiency. Although excellent outcomes have proved the potential of this technique, microorganisms face some obstacles when considering complicated situations in the real field, such as bacterial adaptability and survivability issues. This study made the first attempt to seek solutions to this issue from the air, exploring ureolytic airborne bacteria with resilient features to find a solution to survivability issues. Samples were collected using an air sampler in Sapporo, Hokkaido, a cold region where sampling sites were mostly covered with dense vegetation. After two rounds of screening, 12 out of 57 urease-positive isolates were identified through 16S rRNA gene analysis. Four potentially selected strains were then evaluated in terms of growth pattern and activity changes within a range of temperatures (15-35°C). The results from sand solidification tests using two Lederbergia strains with the best performance among the isolates showed an improvement in unconfined compressive strength up to 4-8 MPa after treatment, indicating a high MICP efficiency. Overall, this baseline study demonstrated that the air could be an ideal isolation source for ureolytic bacteria and laid a new pathway for MICP applications. More investigations on the performance of airborne bacteria under changeable environments may be required to further examine their survivability and adaptability.